2013
DOI: 10.3109/00207454.2013.823605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, demographic and prognostic features of sporadic amyotrophic lateral sclerosis in Northern Turkey

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease for which progression cannot be prevented. In this study, we evaluated 37 patients diagnosed with sporadic definitive-probable ALS who were monitored in our neurology clinic between 2002 and 2012 in terms of age, gender, profession, onset, and clinical course within the disease process. The hospital ethics committee approved the study. Nineteen female and 18 male patients diagnosed with sporadic definitive or probable ALS were evaluated for age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Although these previous studies have shown that the bulbar-onset patients have lower survival rates than limb-onset patients, our results did not support this finding. Most studies have found no difference in survival between male and female patients although there are some registries and small retrospective studies which have shown shorter survival in females, and, conversely, a recent study indicated female gender as a good prognostic factor (15,26,(28)(29)(30). The current study showed no significant difference in MMT and ALSFRS-R deterioration rates between males and females.…”
Section: Discussioncontrasting
confidence: 72%
“…Although these previous studies have shown that the bulbar-onset patients have lower survival rates than limb-onset patients, our results did not support this finding. Most studies have found no difference in survival between male and female patients although there are some registries and small retrospective studies which have shown shorter survival in females, and, conversely, a recent study indicated female gender as a good prognostic factor (15,26,(28)(29)(30). The current study showed no significant difference in MMT and ALSFRS-R deterioration rates between males and females.…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies have shown that smoking is a risk factor for ALS, and that patients who smoke may have shorter survival times as well 22–24. Additionally, some scientists believe that the higher ALS incidence rate in males may be explained by their higher smoking rate, and by the increased chances of exposure to metals and chemicals in the workplace, but the percentage of smokers in male and female patients in our database was lower compared with all Chinese adults in 2002 9 25. Moreover, some studies have suggested that the reason why the prognosis of female patients is better than that of male patients is that metabolism and hormone status differ between males and females 25.…”
Section: Discussionmentioning
confidence: 71%
“…While some attention has been paid to the relationship between geospatial factors and incidence, prevalence, and survival in ALS, [9][10][11][12][13][14][15][16] to our knowledge, the relationship between diagnostic delay in ALS and urban versus rural dwelling is largely unstudied, aside from one paper origininating from the Cantabria region of Northern Spain. 13 While not the focus of this study, the median time to diagnosis did differ between groups (4.8 months for urban vs 9.1 months for rural dwellers); however, there are some limitations with interpreting the significance of this finding; while the total number of patients was 53, there is no documentation of the actual number of rural patients included in the study nor is there any information regarding their distance from the tertiary center.…”
Section: Discussionmentioning
confidence: 99%